2013
DOI: 10.3402/jom.v5i0.19804
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis: keeping the pathos out of the biont

Abstract: The primary goal of the human microbiome initiative has been to increase our understanding of the structure and function of our indigenous microbiota and their effects on human health and predisposition to disease. Because of its clinical importance and accessibility for in vivo study, the oral biofilm is one of the best-understood microbial communities associated with the human body. Studies have shown that there is a succession of select microbial interactions that directs the maturation of a defined communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 123 publications
0
62
0
5
Order By: Relevance
“…To date, however, no phages able to infect P. gingivalis have been identified, and this species has no known naturally occurring plasmids (48,49). Hence, the main function of this system remains unconfirmed.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, no phages able to infect P. gingivalis have been identified, and this species has no known naturally occurring plasmids (48,49). Hence, the main function of this system remains unconfirmed.…”
Section: Discussionmentioning
confidence: 99%
“…gingivalis can cause dysbiosis, inducing a microbial shift that leads to periodontitis [9,17]. Furthermore, P. gingivalis was the most frequent bacteria isolated from chronic periodontitis patients and has been related to disease progression [13,43].…”
Section: Introductionmentioning
confidence: 99%
“…As per PSD model, periodontitis is believed to be initiated by synergistic and dysbiotic microbial communities [21]. Dysbiosis is characterized by the relative abundance of pathobionts, commensals of the biofilm that under certain conditions can cause pathology [22,23], compared to commensals in the biofilm. The results of human clinical studies are in agreement with the observations identified in animal models regarding the PSD model.…”
Section: Oral Biofilmmentioning
confidence: 99%
“…In response to a change in pH or temperature, P. gingivalis alters the biophysical properties of its membrane lipids [22]. Despite being anaerobe, P. gingivalis is microaerotolerant.…”
Section: Host Influence On P Gingivalismentioning
confidence: 99%
See 1 more Smart Citation